(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study aimed to assess the effectiveness of pharmacological correction of atherogenic dyslipidemia in elderly patients with type 2 diabetes mellitus (T2DM) and high cardiovascular risk. A retrospective analysis of 180 outpatient medical records of elderly patients followed for five years was performed. Lipid profile parameters, the frequency and duration of statin therapy, and the rate of achievement of target low-density lipoprotein cholesterol (LDL-C) levels were evaluated. The study revealed low effectiveness of lipid-lowering therapy, which was attributable both to insufficient treatment adherence and to the use of suboptimal statin doses.